دور البرلمان في عملية التعديل الدستوري بين النص والممارسة في التجربة الدستورية الجزائرية - معمر, أ / بوخاتم (Sciences humaines; Vol. 42 (2015): SCIENCES HUMAINES (Novembre ), 2016)
البرلمان في عملية التعديل الدستوري من خلال النصوص من جهة والممارسة من جهة أخرى. حيث أن هناك نصوص تحتمل التأويل ومن خلالها وقعت عملية مراجعة الدستور طبقا لهذه الاتجاهات والتأويلات الخاطئة، وفي هذه الورقة نوضح العديد من النقاط المتعلقة بدور البرلمان سواء من حيث الإقرار    أو الاقتراح، وكذا نقترح العديد     من الحلول لمعالجة الخلل حسب وجهة نظرنا والتي نراها سديدة وجديرة بالنظر.   In this paper, we discuss the role of parliament in the process of constitutional amendment, through the provisions on one hand, and practice on the other one. Where there are texts (provisions) likely to be interpreted through which the constitutional review processes were done in accordance to these trends and interpretations, so in this we are going to clarify several points concerning the role of Parliament, both in terms of approval or proposal, as well as we’ll suggest many of solutions to address the defect by our point of view which we consider judicious and worthy given.